Collocations on the plane: Clark Coolidge and Philip Guston's Poem-Pictures. Issue 8 (14th September 2018) - Wilson, Rachael M.
ABSTRACT: This essay reframes a much remarked shift in Clark Coolidge's poetry, from the atomistic early poems to the longer forms that emerged in the mid-seventies, by focusing this development through the lens of Coolidge's collaboration with Philip Guston. In bringing attention to a relatively neglected body of work – the collaborative portfolio of image-text drawings called 'poem-pictures', and their remediation in the book Baffling Means – this essay shows how the change in Coolidge's poetics circa 1975 corresponds to a prior shift in Guston's painting, circa 1970, from his abstract expressionist to neo-figurative period. I draw on art historian Robert Slifkin's re-reading of Guston's 'return to figuration' through Erich Auerbach and Paul de Man's epistemological and historiographic theories of the figural in order to show how Coolidge, in his collaboration with Guston, unfolds a 'figural' poetics from his earlier literalist and materialist approach to language. The essay redresses the shortfall of analysis of Guston's collaborations with poets in art-historical narratives, while it shows how existing critical discourse misapprehends the change in Coolidge's poetics as a move toward a 'lyrical' mode.